Disarming Strangers : Nuclear Diplomacy with North Korea - Sigal, Leon V. (Book collections on Project MUSE., 2001)
In June 1994 the United States went to the brink of war with North Korea. With economic sanctions impending, President Bill Clinton approved the dispatch of substantial reinforcements to Korea, and plans were prepared for attacking the North's nuclear weapons complex. The turning point came in an extraordinary private diplomatic initiative by former President Jimmy Carter and others to reverse the dangerous American course and open the way to a diplomatic settlement of the nuclear crisis. Few Americans know the full details behind this story or perhaps realize the devastating impact it could ha.